Urban School Nutrition: Student and Teacher Perspectives on Creating a Healthier Food Environment - Rahayu Indriasari; Yessy Kurniati; Safrullah Amir; Indra Fajarwati Ibnu; Balqis Balqis (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Changes in lifestyle and eating habits can affect food choices for adolescents, impacting their nutritional intake. Schools are pivotal in shaping healthy eating behaviors. This qualitative study explores the perspectives of secondary school students and teachers on strategies to improve the healthy food environment in an urban school. Two focus group discussions with students and one with teachers, along with one in-depth interview with the school principal, were conducted at a junior high school in Makassar city. The audio recordings were transcribed and analyzed thematically to identify key themes. Students appeared to be aware of the importance of healthy eating habits; however, they lacked a full understanding of which healthier choices to make. Focus group discussions and interviews revealed that all groups recognize the importance of promoting healthier choices through regulation, education, and accessible nutritious foods. The study highlights actionable strategies for implementing school-based interventions to foster sustainable healthy eating behaviors.